Genetic diversity of Contracaecum rudolphii sp. A (Nematoda: Anisakidae) parasitizing the European Shag Phalacrocorax aristotelis desmarestii from the Spanish Mediterranean coast - Roca-Geronès, Xavier; Fisa, Roser; Montoliu, Isabel; Casadevall, Margarida; Tobella, Carles; Bas, Josep M.; Palomba, Marialetizia; Mattiucci, Simonetta (Frontiers in Veterinary Science, 2023)
Sibling species of the Contracaecum rudolphii (s. l.) complex are habitually endoparasites of cormorants of the Phalacrocoracidae family, worldwide. In Europe, the two species C. rudolphii sp. A and C. rudolphii sp. B have been identified. However, information regarding the occurrence and distribution of these anisakids in cormorants from Spain is scarce. In the present work, 20 specimens of the European Shag, Ph. aristotelis desmarestii from the Western Mediterranean Spanish marine coast were parasitologically analysed for the presence of nematodes. All hosts were found parasitized with Contracaecum specimens (n = 1517). A representative subsample was genetically identified as C. rudolphii sp. A by sequences analysis of the mtDNA cox2 gene and the ITS1 and ITS2 regions of the rDNA. This represents the first report of C. rudolphii sp. A from the Spanish Mediterranean waters. Population genetic analysis was performed including other C. rudolphii sp. A specimens from the West Sardinian and the Tyrrhenian Sea. At the intraspecific level, a significant genetic differentiation (Fst ≈ 0.08, p < 0.00001) between the metapopulation from the Spanish Mediterranean coast and that from the Sardinian waters was observed; whereas, no differentiation was found between metapopulations of the parasite from the Spanish and the Tyrrhenian Italian coast. The findings highly support the hypothesis of the adaptation of the life-cycle of C. rudolphii sp. A in brackish and marine ecosystems. Furthermore, the results on the population genetics of C. rudolphii sp. A suggest the possible role of the migration routes of wintering populations of cormorants in Mediterranean Sea in influencing the parasite genetic structure.